A multicentre evaluation and expert recommendations of use of the newly developed BioFire Joint Infection polymerase chain reaction panel - Kordo Saeed; Nusreen Ahmad-Saeed; Rachel Annett; Gavin Barlow; Lucinda Barrett; Sara E. Boyd; Nicola Boran; Peter Davies; Harriet Hughes; Gwennan Jones; Laura Leach; Maureen Lynch; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)
Septic arthritis is a serious condition with significant morbidity and mortality, routinely diagnosed using culture. The FDA has recently approved the rapid molecular BioFire® Joint Infection Panel (BJIP) for synovial fluid. We aimed to evaluate the BJIP compared to culture and its potential use in patient management. A multicentre retrospective evaluation of BJIP was conducted in the UK and Ireland. Positive percent agreement (PPA) and negative percent agreement (NPA) were calculated between the BJIP and routine culture. A multidisciplinary team (MDT) discussion addressing the optimal or potential case use of the assay practice was facilitated. Three hundred ninety-nine surplus synovial fluid samples (~ 70% from native joints) from eight centres were processed using BJIP in addition to routine culture. An increased yield of positive results was detected using BJIP compared to routine culture (98 vs 83), giving an overall PPA of 91.6% and overall NPA of 93% for the BJIP compared to culture results. The BJIP detected resistant markers and additional organisms that could influence antibiotic choices including Neisseria gonorrhoeae and Kingella kingae . The MDT agreed that the assay could be used, in addition to standard methods, in adult and children patients with specialist advice use based on local needs. Rapid results from BJIP were assessed as having potential clinical impact on patient management. Organisms not included in the panel may be clinically significant and may limit the value of this test for PJI.

Genetic drift drives rapid speciation of an Arctic insular endemic shrew ( Sorex pribilofensis ) - Ben J. Wiens; Fraser J. Combe; Bobette Dickerson; Lauren M. Divine; Veronica M. Padula; George K. Sage; Sandra L. Talbot; Andrew G. Hope (Molecular Ecology, 2022)
Episodes of Quaternary environmental change shaped the genomes of extant species, influencing their response to contemporary environments, which are changing rapidly. Island endemics are among the most vulnerable to such change, accounting for a disproportionate number of recent extinctions. To prevent extinctions and conserve island biodiversity it is vital to combine knowledge of species' ecologies with their complex evolutionary histories. The Bering Sea has a history of cyclical island isolation and reconnection, coupled with modern rates of climate change that exceed global averages. The endangered Pribilof Island shrew ( Sorex pribilofensis ) is endemic to St. Paul Island, Alaska, which was isolated from mainland Beringia ~14,000 years ago by rising sea levels. Using ~11,000 single nucleotide polymorphisms, 17 microsatellites and mitochondrial sequence data, we test predictions about the evolutionary processes driving shrew speciation across Beringia. Our data show considerable differentiation of S. pribilofensis from mainland sibling species, relative to levels of divergence between mainland shrews. We also find a genome‐wide loss of diversity and extremely low N e for S. pribilofensis. We then show that intraspecific genetic diversity is significantly related to interspecific divergence, and that differentiation between S. pribilofensis and other Beringian shrews is highest across loci that are fixed in S. pribilofensis , indicating that strong drift has driven differentiation of this island species. Our findings show that drift as a consequence of Arctic climate cycling can rapidly reshape insular biodiversity. Arctic island species that lack genomic diversity and have evolved in response to past climate may have limited ability to respond to modern environmental changes.

Water table depth modulates productivity and biomass across Amazonian forests - Thaiane R. Sousa; Juliana Schietti; Igor O. Ribeiro; Thaise Emílio; Rafael Herrera Fernández; Hans ter Steege; Carolina V. Castilho; Adriane Esquivel‐Muelbert; Timothy Baker; Aline Pontes‐Lopes; Camila V. J. Silva; Juliana M. Silveira; et al. (Global Ecology and Biogeography, 2022)
Aim Water availability is the major driver of tropical forest structure and dynamics. Most research has focused on the impacts of climatic water availability, whereas remarkably little is known about the influence of water table depth and excess soil water on forest processes. Nevertheless, given that plants take up water from the soil, the impacts of climatic water supply on plants are likely to be modulated by soil water conditions. Location Lowland Amazonian forests. Time period 1971–2019. Methods We used 344 long‐term inventory plots distributed across Amazonia to analyse the effects of long‐term climatic and edaphic water supply on forest functioning. We modelled forest structure and dynamics as a function of climatic, soil‐water and edaphic properties. Results Water supplied by both precipitation and groundwater affects forest structure and dynamics, but in different ways. Forests with a shallow water table (depth Main conclusions We show that the two extremes of water availability (excess and deficit) both reduce productivity in Amazon upland ( terra‐firme ) forests. Biomass and productivity across Amazonia respond not simply to regional climate, but rather to its interaction with water table conditions, exhibiting high local differentiation. Our study disentangles the relative contribution of those factors, helping to improve understanding of the functioning of tropical ecosystems and how they are likely to respond to climate change.

Sources for sedimentary bacteriohopanepolyols as revealed by 16S rDNA stratigraphy - Marco J. L. Coolen; Helen M. Talbot; Ben A. Abbas; Christopher Ward; Stefan Schouten; John K. Volkman; Jaap S. Sinninghe Damsté (Environmental Microbiology, 2008)
Summary Bacteriohopanoids are widespread lipid biomarkers in the sedimentary record. Many aerobic and anaerobic bacteria are potential sources of these lipids which sometimes complicates the use of these biomarkers as proxies for ecological and environmental changes. Therefore, we applied preserved 16S ribosomal RNA genes to identify likely Holocene biological sources of bacteriohopanepolyols (BHPs) in the sulfidic sediments of the permanently stratified postglacial Ace Lake, Antarctica. A suite of intact BHPs were identified, which revealed a variety of structural forms whose composition differed through the sediment core reflecting changes in bacterial populations induced by large changes in lake salinity. Stable isotopic compositions of the hopanols formed from periodic acid‐cleaved BHPs, showed that some were substantially depleted in 13 C, indicative of their methanotrophic origin. Using sensitive molecular tools, we found that Type I and II methanotrophic bacteria (respectively Methylomonas and Methylocystis ) were unique to the oldest lacustrine sediments (> 9400 years BP), but quantification of fossil DNA revealed that the Type I methanotrophs, including methanotrophs related to methanotrophic gill symbionts of deep‐sea cold‐seep mussels, were the main precursors of the 35‐amino BHPs (i.e. aminopentol, ‐tetrol and ‐triols). After isolation of the lake ∼3000 years ago, one Type I methanotroph of the ‘methanotrophic gill symbionts cluster’ remained the most obvious source of aminotetrol and ‐triol. We, furthermore, identified a Synechococcus phylotype related to pelagic freshwater strains in the oldest lacustrine sediments as a putative source of 2‐methylbacteriohopanetetrol (2‐Me BHT). This combined application of advanced geochemical and paleogenomical tools further refined our knowledge about Holocene biogeochemical processes in Ace Lake.